دراسة تجريبية لتحديد سلوك التماسك في البيتون ذاتي الارتصاص المصنع من مواد محلية المنشأ - تريكية, علي (Latakia University Journal -Engineering Sciences Series, 2019)
نقوم في هذا البحث باختبار آلية التماســك بين فولاذ التســـــليح والخرسانة، حيث تم إجراء الاختبارات على الخرســـانة التقليدية) conventional vibrated concrete - CVC) وعلى الخرســـــانة ذاتية الارتصاص SCC ) - self-compacting concretes)) بهدف دراسة تأثير أنواع الاسمنت البورتلاندي العادي الأسود بصنفيه الأول (32.5Mpa) - I , والثاني (42.5Mpa) - II المستخدمة في تصنيع خلطات الاختبار, وذلك على التماسك بين الخرسانة بنوعيها (SCC,CVC) والقضبان الفولاذية . تم تحميل عينات الاختبار وفق معدل ثابت وتمَّ تسجيل كل من انزلاق القضبان والحمولة المطبقة خلال إجراء الاختبارات حتى الوصول إلى انهيار التماسك والانسحاب الموافق له. تُبين نتائِج الاختبارات والتي تمَّ إجراؤها على عينات بقياس(150mm) بأن قٍوى التماسك بين الخرسانة وقضبان التســليح ترتبط بقطر القضيب، وبنوع الإسمنت المستخدم وبنوع الخرسانة (تقليدية أم ذاتية الارتصاص). تُبينْ النتائج التي تمَّ الحصول عليها على ازدياد مقاومة الخرسانة على الضغط وازديادْ قوى التماسك بين فولاذ التسليح والخرسانة وذلك للخرسانة العادية ( CVC) وللخرسانة ذاتية الارتصاص (SCC) عندما استخدمنا الاسمنت البورتلاندي الأسود من صنف (42.4 Mpa) - II عنه من صنف (32.5Mpa) - I . In this paper, we test the mechanism of bond between reinforcing steel and concrete, where the tests were carried out on the conventional vibrated concrete CVC and self-compacting concretes SCC to study the effect of the ordinary black Portland cement with its first I- (32.5Mpa) And the second II-(42.5Mpa) used in the manufacture of test mixtures, on the bond between concrete (SCC, CVC) and steel bars. Test samples were loaded at a fixed rate and both the sliding bars and load applied during the tests were recorded until the collapse of cohesion and corresponding withdrawal was achieved. The samples were loaded according to a fixed rate and recording of both sliding rods and load applied during the tests. The results of the tests, which were conducted on 150 mm samples, show that the bonding forces between the concrete and the reinforcement bars are related to the diameter of the penis, the type of cement used and the type of concrete mix. The results obtained showed an increase in resistance to pressure and increased strength between reinforcing steels and concrete for CVC and self-tapping concrete when we used black Portland cement of( 42.4 Mpa) type (32.5Mpa).